Analisis Kinerja Keuangan Berdasarkan Rasio Profitabilitas Pada Koperasi Unit Desa (KUD) Sawit Mandiri Desa Talang Makmur Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat Provinsi Jambi - Dewi Fitriyana; Agustina Mutia; Rohana Rohana (CV. Aksara Global Akademia, 2023)
This study aims to determine the financial performance of the Sawit Mandiri Village Unit Cooperative (KUD) in Talang Makmur Village, Tebing Tinggi District when analyzed in terms of Profitability Ratios using Return On Assets (ROA), Return On Equity (ROE), and Service Operational Independence (BOPO). The method used in this research is descriptive qualitative research in the form of financial ratio analysis based on the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 06/Per/Dep.0/IV/2016 concerning Guidelines for Health Assessment of Savings and Loans Cooperatives Cooperative Savings and Loans Unit. The results of this study indicate that the financial performance of the Sawit Mandiri Village Unit Cooperative (KUD) in 2018-2022 based on Return on Assets (ROA) is considered low, this is based on the results of calculating the average Return on Assets (ROA) for 5 years, namely 8, 64%, in the unfavorable criterion, it is still far below the cooperative Return on Asset (ROA) standard, which is 10%. Based on Return on Equity (ROE) it is considered low, this is based on the results of calculating the average Return on Equity (ROE) for 5 years, namely 14.50%, in the criteria in very good criteria it meets the cooperative Return on Equity (ROE) standard, namely large 5%. Based on Service Operational Independence (BOPO) it is considered high, this is based on the calculation results of the average Service Operational Independence (BOPO) for 5 years, namely 9.92%, in very good criteria it meets the cooperative standard Service Operational Independence (BOPO), which is 100% .